Dynamic Interaction Between Deforestation and Rice Cultivation During the Holocene in the Lower Yangtze River, China - He, Keyang; Lu, Houyuan; Sun, Guoping; Wang, Yonglei; Zheng, Yunfei; Zheng, Hongbo; Lei, Shao; Li, Yongning; Zhang, Jianping (Frontiers in Earth Science, 2022)
Human activity has transformed the Earth’s landscapes pervasively for thousands of years and the most important anthropogenic alteration was the clearing of forests and establishment of agriculture. As a center of rice domestication and early population growth, the lower Yangtze River has been transformed extensively in the Holocene. However, the timing, extent and process of deforestation and its relationship with the intensification of rice cultivation remains controversial. Here, four representative archaeological sites ranging from 8100 to 4300 cal. a BP, i.e., Jingtoushan, Hemudu, Yushan and Xiawangdu sites, were selected for detailed palynological analysis and evidences of anthropogenic deforestation and subsistence strategy were also synthesized to investigate dynamic human-forest interaction. Though natural vegetation had already been altered at the Jingtoushan site around 8000 cal. a BP, it was more likely to be management of acorns by limited burning to open habitats and increase yield. As the subsistence shifted from acorn exploitation towards rice cultivation after 6000 cal. a BP, real deforestation for agriculture may occur at the Yushan and Xiawangdu sites due to conflict on labour input and land use. However, these deforestations were just confined to the archaeological sites at local scale and no consistent vegetation change occurred at regional scales induced by human activities until the last 3000 yr.